Disparitas Penilaian Kinerja Keuangan Melalui ROI DAN EVA - Nur Wahyuning Sulistyowati; Dewi Santika Risti; Supri Wahyudi Utomo (JAK (Jurnal Akuntansi) Kajian Ilmiah Akuntansi, 2024)
Knowing the differences in the financial performance of PT Kino Indonesia Tbk for the 2017-2021 period, using the return on investment (ROI) and economic value added (EVA) methods as the purpose of this research. This type of comparative descriptive research with secondary data sources of the financial reports of PT Kino Indonesia Tbk from 2017-2021. Research has resulted that PT Kino's financial performance when assessed using the ROI method shows the best in 2019, as evidenced by the increase in the 2019 ROI value of 6.9% from the previous year. The company's ROI still shows a positive value, so that the company is considered capable of providing results to investors. Based on the results of EVA calculations, the company PT Kino Indonesia Tbk, is unable to provide added value to funders as evidenced from 2017-2021, with EVA values showing negative values or EVA below zero values.